EVALUASI SIFAT FISIK NUGGET BERBAHAN BAKU SURIMI BELUT (Monopterus albus) - Iin Khusnul Khotimah; Dewi Kartika Sari (Faculty of Agricultural Technology, University of Jember, 2007)
An experiment on nugget processing using surimi of eel fish had been done. Aim of the experiment was to find the best concentration of cassava starch (tapioca) for increasing the usage of eel fish and enhancing its sensory quality. The experiment was completely randomized with four treatments of tapioca concentration (20%, 30%, 40% and 50% w/w). The data showed that the different tapioca concentration do not influence water and protein content of nugget product, nevertheless the different concentration of tapioca affected organoleptic quality of nugget. Concentration of tapioca treatment by 20% resulted the best quality of fish nugget product, and was most likely than the other three concentrations. The average of its organoleptic score for color, flavor, texture, and taste were 5.20 (like), 4.30 (rather like), 4.85 (like), and 5.40 (like), respectively. Keywords: nugget, surimi, eel fish